(3QSGdI aj GdWHs
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3heG EdG Efge dGjJecfhf ai GdMGd ef GdGOhjI GdJi LQHhgG ajgG aCNPhG GdEfJbGd ef GdTF Edi THgg s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3GdSQWGf hQbe UdH dg ai GdLSO CUd cHjQ hJSbjg ZQhb NVQ eeJdFg heG CShg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYI hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs